Bacterial biofilm composition in caries and caries-free subjects - Wolff, Diana; Frese, Cornelia; Maier-Kraus, Theresa; Wolff, Björn (Caries research, 2013)
Background: Certain major pathogens such as Streptococcus mutans, Lactobacillus spp. and others have been reported to be involved in caries initiation and progression. Yet, in addition to those leading pathogens, microbial communities seem to be much more diverse and individually differing. The aim of this study, therefore, was to analyze the bacterial composition of carious dentin and the plaque of caries-free patients by using a custom-made, real-time quantitative polymerase chain reaction assay (RQ-PCR). Methods: The study included 26 patients with caries and 28 caries-free controls. Decayed tooth substance and plaque samples were harvested. Bacterial DNA was extracted and tested for the presence of 43 bacterial species or species groups using RQ-PCR. Results: Relative quantification revealed that Propionibacterium acidifaciens was significantly more abundant in caries samples than were other microorganisms (fold change 169.12, p = 0.023). In the caries-free samples, typical health-associated species were significantly more prevalent. Unsupervised hierarchical cluster analysis showed a high abundance of P. acidifaciens in caries subjects and distinct but individually differing bacterial clusters in the caries-free subjects. The distribution of 11 bacteria allowed full discrimination between caries and caries-free subjects. Conclusion: Within the investigated cohort, P. acidifaciens was the only pathogen significantly more abundant in caries subjects. Cluster analysis yielded a diverse flora in caries-free subjects, whereas it was narrowed down to a small range of a few outcompeting members in caries subjects.
Published online: November 09, 2012
Gesehen am 08.10.2018